Effect of coconut (Cocos nucifera L.) water of different fruit maturity stages on axillary bud initiation, growth and development of plantain (Musa AAB.) - Mintah, L.O.; Arhin, L.; Ofosu-Anim, J.; Nkansah, G.O. (Journal of Applied Horticulture, 2018)
The effect of endogenous content of cytokinin (trans- zeatin riboside, T-ZR) and auxin (indole-3-acetic acid, IAA) in coconut water from fruits at four different fruit maturity stages: liquid endosperm, solid endosperm formation stage, semi matured endosperm stage and fully matured dried fruit stage on proliferation of axillary bud initiation and development of local plantain cultivar (cv. Asamienu, Musa AAB) was investigated at the University of Ghana Forest and Horticultural Crops Research Centre, Kade. The results indicated that the IAA content decreased while the T-ZR content increased with fruit maturity. Three weeks after treatments, the highest number of well-differentiated axillary buds was obtained for suckers treated with coconut water from fruits at liquid endosperm formation stage whilst the highest number of fully developed plantlets was produced from treatments with coconut water at semi-endosperm formation stage. One month after the application of the split corm technique, the highest number of additional well-differentiated axillary buds and fully developed plantlets were produced from treatments with coconut water at the liquid endosperm formation stage. In general, treatments with coconut water from fully matured dried fruits produced the largest and the most vigorously growing plantlets. © 2018 Society for Advancement of Horticulture. All rights reserved.
Keywords: Axillary bud; Coconut water; Indole-3-acetic acid; Plantain; Trans- zeatin riboside